Molecular docking and molecular dynamics simulation identify a novel Radicicol derivative that predicts exclusive binding to Plasmodium falciparum Topoisomerase VIB. Issue 15 (29th August 2022) - Bansod, Shephali; Raj, Navya; R, Amjesh; Nair, Achuthsankar S.; Bhattacharyya, Sunanda
Abstract: Plasmodium falciparum harbors a unique type II topoisomerase, Topoisomerase VIB ( Pf TopoVIB), expressed specifically at the actively replicating stage of the parasite. An earlier study showed that Radicicol inhibits the decatenation activity of Pf TopoVIB and thereby arrests the parasites at the schizont stage. Radicicol targets a unique ATP-binding fold called the Bergerat fold, which is also present in the N-terminal domain of the heat shock protein 90 ( Pf Hsp90). Hence, Radicicol may manifest off-target activity within the parasite. We speculate that the affinity of Radicicol towards Pf TopoVIB could be enhanced by modifying its structure so that it shows preferential binding towards Pf TopoVIB but not to Pf Hsp90. Here, we have performed the docking and affinity studies of 97 derivatives (structural analogs) of Radicicol and have identified 3 analogs that show selective binding only to Pf TopoVIB and no binding with Pf Hsp90 at all. Molecular dynamics simulation study was performed for 50 ns in triplicate with those 3 analogs and we find that one of them shows a stable association with Radicicol. This study identifies the structural molecule which could be instrumental in blocking the function of Pf TopoVIB and hence can serve as an important inhibitor for malaria pathogenesis. Communicated by Ramaswamy H. Sarma